Isolation and characterization of an iodide bridged dimeric palladium complex in carbonylation of methanol - Tonde, S. S.; Kelkar, Ashutosh A.; Bhadbhade, Mohan M.; Chaudhari, Raghunath V. (Journal of Organometallic Chemistry, 2005)
Palladium-catalyzed carbonylation of methanol in presence of iodide promoters was investigated. Iodide bridged palladium dimeric complex, [PPh3CH3](2)[Pd2I6] was isolated from the carbonylation reaction mixture and characterized using X-ray crystallography. Reaction mechanism was proposed based on IR and UV spectroscopic characterizations of catalytic species involved in the catalytic cycle. The isolated dimeric palladium species, [Pd2I6](2-) underwent carbonylation to give monomeric species [PdI3CO](-) at atmospheric pressure of carbon monoxide. It was also observed that PPh3 plays an important role to avoid catalyst deactivation at higher temperatures. Turnover frequency (TOF) of 1052 h(-1) was achieved using Pd(OAC)(2)-HI-PPh3 catalyst system at 175 degrees C. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: dirneric palladium; IR spectroscopy; methanol carbonylation; palladium catalyst; reaction mechanism; UV

Biphasic hydroformylation of 1,4-diacetoxy-2-butene: a kinetic study - Chansarkar, Rashmi; Kelkar, Ashutosh A.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2007)
Hydroformylation of 1,4-diacetoxy-2-butene was studied using a water-soluble Rh complex catalyst prepared in situ from [Rh(COD)Cl](2) complex and trisodium salt of tri-(m-sulfophenyl)phosphine (TPPTS) in a biphasic system. The sequence of addition of catalyst precursor, ligand, and reactant/solvent showed a significant effect on leaching of Rh from aqueous to organic phase, and hence, the procedure was optimized to develop a nonleaching and stable biphasic catalyst system. The only hydroformylation product (1,4-diacetoxy-2-formyl butane, DAFB) formed was found to deacetoxylate completely to 2-formyl-4-acetoxybutene (FAB), thus allowing a one-pot synthesis of FAB, an important intermediate for Vitamin A. Experimental data on the concentration-time and CO/H-2 consumption-time profiles were obtained, and the effects of DAB concentration, CO partial pressure, H-2 partial pressure, and catalyst concentration were studied in a stirred batch reactor over a temperature range of 338-358 K. The effect of aqueous phase holdup on the initial rate of hydroformylation and analysis of gas-liquid and liquid-liquid mass transfer effects were also investigated to identify the reaction rate data operating in a kinetic regime. A rate equation based on the known hydroformylation reaction mechanism was used to fit the experimental rate data and to evaluate kinetic parameters. The agreement between the model prediction and the experimental data was found to be excellent. The activation energy was calculated as 30.1 kJ/mol. The biphasic catalyst system reported here is not only efficient for catalyst-product separation but also provides a tandem synthesis of Vitamin A intermediate, FAB.

Ultrasound promoted asymmetric transfer hydrogenation of ketones using Ru(II)arene/amino alcohol catalyst system - Shingote, Savita K.; Kelkar, Ashutosh A.; Borole, Yogesh L.; Joshi, Pradip D.; Chaudhari, Raghunath V. (Ultrasonics Sonochemistry, 2008)
Asymmetric transfer hydrogenation of ketones using Ru(II)arene/amino alcohol catalyst system proceeds with significant rate enhancement by ultrasound promotion. Comparison of the silent reactions carried out at 25 degrees C with reactions under sonochemical activation at 25 degrees C clearly showed enhancement in catalytic activity by 5-10 times without significantly affecting the enantioselectivity. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: asymmetric catalysis; transfer hydrogenation; Ultrasound

Hydroesterification of 2-vinyl-6-methoxynaphthalene using palladium complexes containing chelating nitrogen ligands - Atla, Shashi B.; Kelkar, Ashutosh A.; Chaudhari, Raghunath V. (Journal of Molecular Catalysis A-Chemical, 2009)
Hydroesterification of 2-vinyl-6-methoxynaphthalene (VMN) to methyl ester of 6-methoxy naphthyl propionic acid (ester of naproxen) has been investigated using palladium complexes containing the chelating N(boolean AND)O and N(boolean AND)N ligands (pyridine-2-carboxylate, 2-acetylpyridine, 2-pyridine-carboxaldehyde, and bipyridine) as catalysts. Palladium complex containing 2-acetylpyridine as the ligand was found to be superior to other Pd-complexes. Both acid and halide promoters were necessary for high activity and selectivity. As an acid promoter, benzenesulfonic acid was found to be more effective compared to p-toluenesulfonic acid. Formation of ether 2-methoxy-6-(1-methoxyethyl)naphthalene and a polymer of VMN was observed in all the reactions. It was observed that active catalytic species generated during carbonylation reaction was responsible for the polymer formation. The effect of various parameters such as solvents, CO pressure, and alcohols on the catalytic activity as well as the selectivity was investigated. The turnover frequency using the complex Pd(acpy)(PPh(3))(OTs)(2) (acpy = 2-acetylpyridine) catalyst was found to be 42 h(-1), which is the highest for the hydroesterification of VMN. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Carbonylation; Hydroesterification; Naproxen; Palladium complex; Polymer of VMN; Promoters

Hydroformylation of 1,4-diacetoxy-2-butene using HRh(CO)(PPh3)(3) tethered on alumina as a catalyst: kinetic study - Chansarkar, Rashmi; Kelkar, Ashutosh A.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2009)
Hydroformylation of 1,4-diacetoxy-2-butene (DAB) was studied using [HRh(CO)(PPh3)(3)] complex catalyst tethered on alumina using phosphotungstic acid (PTA) as an anchoring agent, with the aim to understand the product distribution, selectivity, and intrinsic kinetics. It was observed that with the tethered heterogeneous catalyst a simultaneous hydroformylation followed by deacetoxylation steps was possible, which is relevant for combining two steps in the sequence of synthesis of vitamin-A intermediate [2-formyl-4-acetoxy butene (FAB)]. P-31 cross-polarization magic angle spinning nuclear magnetic resonance (CP MAS NMR) and infrared (IR) instrumental techniques were found be the most effective techniques to establish the catalyst structure and true heterogeneity. On the basis of the spectroscopic evidence, we postulate the loss of a PPh3 group during tethering to give HRh(CO)(PPh3)(2)-PTA-Al2O3 as a heterogeneous complex catalyst. Experimental data on the concentration-time and CO/H-2 consumption-time profiles were obtained and the effects of DAB concentration, CO partial pressure, H-2 partial pressure, and catalyst loading were studied in a 50 mL stirred batch reactor over a temperature range of 338-358 K. The analysis of solid-liquid-gas mass transfer effects was investigated to ensure that the reaction was operating in the kinetic regime Various models were developed, and the best model was chosen by a model discrimination procedure. The agreement between the model prediction and the experimental data was found to be excellent. The activation energies for the hydroformylation and deacetoxylation steps were found to be 42.5 and 80.2 kJ/mol.

Kinetics of arylation of 3-bromo-benzophenone with n-butylacrylate using NC palladacycle catalyst - Atla, Shashi B.; Rajurkar, Kalpendra B.; Kelkar, Ashutosh A.; Chaudhari, Raghunath V. (Journal of Molecular Catalysis A-Chemical, 2009)
The kinetics of arylation of n-butylacrylate (n-BA) with 3-bromo-benzophenone (BBP) using a monomeric palladacycle complex [Pd(ppy)(PPh(3))(OTs)](ppy=2-phenylpyridine) catalyst has been studied. The effect of concentration of the substrate, base (NaOAc), and catalyst was studied at three different temperatures (413-433 K). The rate was found to be first order with respect to catalyst, first order tending to zero order with respect to n-butylacrylate and NaOAc concentrations. The rate passed through a maximum with variation of BBP concentration. The observed results have been explained on the basis of formation of Pd species (PdX(2), PdX(3)(-), PdX(4)(2-), and Pd(2)X(6)(2-)) which are inactive for the Heck reaction. Various empirical rate equations were considered to fit the rate data and the best fitting model has been selected. The rates predicted by model were found to be in good agreement with the observed experimental data. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Arylation; Heck reaction; kinetics; Palladacycle

Mass transfer and solubility of CO and H-2 in ionic liquid. case of [Bmim][PF6] with gas-inducing stirrer reactor - Sharma, Amit; Julcour, Carine; Kelkar, Ashutosh A.; Deshpande, Raj Madhukar; Delmas, Henri (Industrial & Engineering Chemistry Research, 2009)
Since the past decade, ionic liquids have gained significant importance as alternative solvents for catalysis applications. Many of the reactions evaluated in ionic liquids employ gases as substrates, and therefore it is important to know their solubility and mass transfer characteristics. This work reports for the first time both the solubility and volumetric gas-liquid mass transfer coefficient k(La) for hydrogen and carbon monoxide in 1-n-butyl-3-methylimidazolium hexafluorophosphate ([Bmim][PF6]) at three temperatures (293, 323, and 373 K) in relevance to hydroformylation reaction. The experimental data on the volumetric gas-liquid mass transfer coefficient are described by a dimensionless correlation for the bench-scale stirred tanks with gas-inducing impeller. k(La) values have also been evaluated for different [Bmim][PF6]-decane emulsions at 373 K.

NC palladacycles in the Heck arylation of ethylene: synthesis, structure and their reactivity - Atla, Shashi B.; Kelkar, Ashutosh A.; Puranik, Vedavati G.; Bensch, Wolfgang; Chaudhari, Raghunath V. (Journal of Organometallic Chemistry, 2009)
Monomeric cyclopalladated complexes with NC coordination using ligands 2-phenylpyridine, 2-phenylquinoline, 8-methylquinoline have been synthesized and the structures have been determined by single crystal X-ray structure analysis. The crystal structures of monomeric palladacycles prepared using benzophenone oxime, and 2-phenylpyridine have also been determined. The use of these complexes in the Heck arylation of ethylene with 2-bromo-6-methoxynaphthalne (BMN) to give 2-vinyl-6-methoxynapthalene which is an intermediate for the synthesis of anti-inflammatory drug Naproxen has been examined and also arylation of ethylene with 3-bromo-benzophenone and 4-bromo-isobutylbenzene was investigated. These palladacycles with NC coordination show excellent catalytic activity with a TOF > 4000 h (1). (C) 2008 Elsevier B.V. All rights reserved.
Keywords: alpha-Aryl propionic acids; Arylation; Palladacycle

Catalytic asymmetric transfer hydrogenation of ketones using [Ru(p-cymene)Cl-2](2) with chiral amino alcohol ligands - Deshpande, Sudhindra H.; Kelkar, Ashutosh A.; Gonnade, Rajesh G.; Shingote, Savita K.; Chaudhari, Raghunath V. (Catalysis Letters, 2010)
Catalytic asymmetric transfer hydrogenation of aromatic alkyl ketones has been investigated using [Ru(p-cymene)Cl-2](2) and new derivatives of beta-amino alcohols synthesized from (S)-(-)-lactic acid and mandelic acid as ligands. Chiral secondary alcohols were obtained with good to excellent conversion (60-90%) and moderate to good enantioselectivities (40-86%). Asymmetric transfer hydrogenation of ketones has been investigated using [Ru(p-cymene)Cl-2](2) and beta-amino alcohols synthesized from (S)-(-)-lactic acid and Mandelic acid as ligands. Chiral secondary alcohols were obtained with good to excellent conversion (60-90%) and moderate to good enantioselectivities (40-86%).
Keywords: Amino alcohol ligand; Asymmetric transfer hydrogenation; Ketones; Ru catalyst

Hydroformylation of 1-octene using [Bmim][PF6]-decane biphasic media and rhodium complex catalyst: thermodynamic properties and kinetic study - Sharma, Amit; Lebigue, Carine Julcour; Deshpande, Raj Madhukar; Kelkar, Ashutosh A.; Delmas, Henri (Industrial & Engineering Chemistry Research, 2010)
A chemical reaction engineering approach is reported to investigate the biphasic hydroformylation of I-octene using [bmim][PF6] ionic liquid. It is based both on a process parameter investigation (temperature, concentrations, and pressures) and a thermodynamic study of the reaction medium (gas liquid and liquid liquid equilibria). Initial rate data show complex behavior with respect to operating parameters and are best described by a rate equation based on a mechanistic model. Complete reaction scheme including isomerization is then modeled accounting from the time dependent concentration of the organic substrates measured in organic phase and recalculated in ionic liquid phase from liquid liquid equilibria.

Oxidation of propane to acrylic acid and acetic acid over alkaline earth-doped Mo-V-Sb-O-x catalysts - Chaudhari, Chandan S.; Sable, Shailesh S.; Gurav, Hanumant; Kelkar, Ashutosh A.; Rane, Vilas H. (Journal of Natural Gas Chemistry, 2010)
Alkaline earth metal (Mg, Ca, Sr and Ba)-doped Mo-V-Sb-O-x catalysts, prepared by a dry-up method, have been investigated for their catalytic performance in the oxidation of propane under different reaction conditions. The catalysts have been characterized by N-2 adsorption-desorption, temperature-programmed desorption (TPD) of NH3, SEM and XRD. Influence of water vapor on the catalytic performance, particularly on the selectivities to acetic acid and acrylic acid, has also been studied. The selectivity to acrylic acid was improved significantly by the doping of alkaline earth metals to Mo-V-Sb-O-x catalysts. The surface acidic sites of the catalyst decreased with the doping of the catalyst with alkaline earth metals, which ultimately was found to be beneficial for obtaining high selectivity to acrylic acid. The catalytic activity and product selectivities were found to be influenced by the reaction temperature, C3H8/O-2 ratio and space velocity. A significant improvement in the selectivity to acrylic acid has also been observed by the addition of water vapor in the feed of propane and oxygen in the oxidation of propane.
Keywords: Acetic acid; acrylic acid; alkaline earth doped Mo-V-Sb-O-x catalysts; oxidation of propane; Surface acidity

Synthesis of acrolein by gas-phase dehydration of glycerol over silica supported bronsted acidic ionic liquid catalysts - Munshi, Mudassir K.; Lomate, Samadhan T.; Deshpande, Raj Madhukar; Rane, Vilas H.; Kelkar, Ashutosh A. (Journal of Chemical Technology and Biotechnology, 2010)
BACKGROUND: Glycerol has become readily available as a byproduct from the biodiesel industry. High functionality and relatively low price make it a potential building block to produce value-added derivatives such as acrolein. RESULTS: Dehydration of glycerol to acrolein was performed over several silica supported Bronsted acidic ionic liquids as catalysts. All the catalysts prepared were active for the synthesis of acrolein (conversion of glycerol was observed in the range 35-90% with selectivity to acrolein in the range 29-58%). CONCLUSIONS: Catalyst prepared from triphenyl (3-sulfopropyl) phosphonium 4-methylbenzenesulfonate gave good activity and selectivity at 4 h reaction time. The conversion of glycerol decreased with increase in glycerol concentration. Higher temperature (325 degrees C) resulted in significantly lower conversion as well as selectivity to acrolein. With the use of two additional traps cooled to -7 degrees C, the selectivity to acrolein increased significantly for good catalysts. (C) 2010 Society of Chemical Industry
Keywords: acidic ionic liquids; acrolein; glycerol dehydration; supported catalyst

Kinetics of hydroformylation of 1-octene in ionic liquid-organic biphasic media using rhodium sulfoxantphos catalyst - Deshpande, R. M.; Kelkar, Ashutosh A.; Sharma, A.; Julcour-Lebigue, C.; Delmas, Henri (Chemical Engineering Science, 2011)
Biphasic hydroformylation of 1-octene was performed using rhodium sulfoxantphos catalyst dissolved in [BuPy][BF(4)] ionic liquid. Preliminary experiments proved this system to retain the catalytic complex within the ionic liquid phase and to maintain a high selectivity towards the linear aldehyde (n:iso ratio of 30) over several cycles. Process parameter investigation showed a first order dependence of the initial rate with respect to the catalyst and 1-octene concentrations, but a more complex behavior with respect to hydrogen (fractional order) and carbon monoxide partial pressures (inhibition at high pressures). Different mathematical models were selected based on the trends observed and evaluated for data fitting. Also, rate models were derived from a proposed mechanism, using Christiansen matrix approach. To calculate concentrations of substrates in the catalytic phase as required by this kinetic modeling, solubility measurements were preformed for the gases (pressure drop technique), as well as for 1-octene and n-nonanal (thermogravimetry analysis). (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Biphasic catalysis; Butylpyridinium tetrafluoroborate; kinetics; Parameter identification; Reaction engineering; solubility

Synthesis of glycidol from glycerol and dimethyl carbonate using ionic liquid as a catalyst - Gade, Swapna M.; Munshi, Mudassir K.; Chherawalla, Batul M.; Rane, Vilas H.; Kelkar, Ashutosh A. (Catalysis Communications, 2012)
Transesterification of dimethyl carbonate with glycerol has been investigated using various ionic liquids as catalysts. Synthesis of glycidol with high selectivity (78%) has been achieved using tetramethylammonium hydroxide ([TMA][OH]) as a catalyst at 80 degrees C. Effect of various reaction conditions on the activity and selectivity was investigated and catalyst concentration had a significant influence on conversion as well as selectivity to glycidol. Activity as well as selectivity of the catalyst decreased significantly with increase in moisture content. Recycle experiment indicated slight drop in glycerol conversion and selectivity to glycidol because of dilution of reaction mixture and also the presence of products from the initial experiment. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Glycerol carbonate; Glycidol; Ionic liquid; Transesterification of glycerol

1,8-Diazabicyclo[5.4.0]undec-7-ene (DBU): a highly efficient catalyst in glycerol carbonate synthesis - Munshi, Mudassir K.; Gade, Swapna M.; Mane, Manoj V.; Mishra, Deepti; Pal, Sourav; Vanka, Kumar; Rane, Vilas H.; Kelkar, Ashutosh A. (Journal of Molecular Catalysis A-Chemical, 2014)
Transesterification of dimethyl carbonate (DMC) with glycerol (GLY) was investigated using various amines as catalysts. Amidines like 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) and 1,5-diazabicyclo[4.3.0]non-5-ene (DBN) were found to be the best catalysts for this reaction. Best results: 98% conversion of GLY with 96% selectivity to GC (TON: 9408), were obtained with DBU as a catalyst. Effect of various reaction conditions on activity and selectivity were investigated using DBU as catalyst. The mechanism of the reaction was investigated with the help of H-1, C-13 and N-15 NMR analysis and OFT calculations. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: DBU; Glycerol; Glycerol carbonate; transesterification

Asymmetric transfer hydrogenation of imines in water/methanol co-solvent system and mechanistic investigation by DFT study - Shende, Vaishali S.; Shingote, Savita K.; Deshpande, Sudhindra H.; Kuriakose, Nishamol; Vanka, Kumar; Kelkar, Ashutosh A. (RSC Advances, 2014)
Asymmetric transfer hydrogenation of various cyclic imines proceeded efficiently with water/methanol co-solvent media in 20 min with excellent yields and enantioselectivities by employing Rh-TsDPEN catalyst and sodium formate as a hydrogen donor. The role of the co-solvent in enhanced productivity of the reaction was investigated by DFT. The mechanism for ATH of the imines has been discussed on the basis of the DFT study.

Efficient synthesis of glycerol carbonate/glycidol using 1,8-diazabicyclo [5.4.0] undec-7-ene (DBU) based ionic liquids as catalyst - Munshi, Mudassir K.; Biradar, Pradeep S.; Gade, Swapna M.; Rane, Vilas H.; Kelkar, Ashutosh A. (RSC Advances, 2014)
Transesterification of dimethyl carbonate with glycerol to glycerol carbonate has been catalyzed efficiently using basic ionic liquids as catalysts. Activity of all the ILs tested is very high and the best result (96% conversion with 82% selectivity to glycerol carbonate and 18% selectivity to glycidol) was obtained using IL1 as catalyst. The effect of catalyst loading has significant influence on the selectivity pattern. The higher activity of the ionic liquid is explained with a plausible mechanism based on the co-operative effect of both cation and anion.

Role of cation-anion cooperation in the selective synthesis of glycidol from glycerol using DABCO-DMC ionic liquid as catalyst - Munshi, Mudassir K.; Gade, Swapna M.; Rane, Vilas H.; Kelkar, Ashutosh A. (RSC Advances, 2014)
Transesterification of dimethyl carbonate with glycerol has been investigated using 1,4-diazabicyclo [2.2.2] octane (DABCO) based ionic liquid as a catalyst. DABCO reacted with dimethyl carbonate to form ionic liquid as the reaction progressed. Though the basicity of DABCO based ionic liquid was lower than that of DABCO, the catalytic activity and selectivity to glycidol was higher with DABCO based ionic liquid as a catalyst, indicating that basicity may not be the only criterion in deciding activity and selectivity of the reaction. The cooperative effect of the cation and anion of the ionic liquid is responsible for the observed results. The best results (97% glycerol conversion with 83% selectivity to glycidol and 17% selectivity to glycerol carbonate) were obtained using DABCO based ionic liquid as a catalyst. A plausible mechanism involving the role of both the cation and anion of the ionic liquid has been proposed.

Asymmetric transfer hydrogenation of imines in water by varying the ratio of formic acid to triethylamine - Shende, Vaishali S.; Deshpande, Sudhindra H.; Shingote, Savita K.; Joseph, Anu; Kelkar, Ashutosh A. (Organic Letters, 2015)
Asymmetric transfer hydrogenation (ATH) of imines has been performed with variation in formic acid (F) and triethylamine (T) molar ratios in water. The F/T ratio is shown to affect both the reduction rate and enantioselectivity, with the optimum ratio being 1.1 in the ATH of imines with the Rh-(1S,2S)-TsDPEN catalyst. Use of methanol as a cosolvent enhanced reduction activity. A variety of imine substrates have been reduced, affording high yields (94-98%) and good to excellent enantioselectivities (89-98%). In comparison with the common azeotropic F-T system, the reduction with 1.1/1 F/T is faster.

Conversion of concentrated sugar solutions into 5-hydroxymethyl furfural and furfural using Bronsted acidic ionic liquids - Matsagar, Babasaheb M.; Munshi, Mudassir K.; Kelkar, Ashutosh A.; Dhepe, Paresh Laxmikant (Catalysis Science & Technology, 2015)
Catalytic amounts of recyclable Bronsted acidic ionic liquids (BAILs) yielded HMF (73%) and furfural (81%) with high selectivity from highly concentrated solutions of D-fructose (40 wt%) and D-xylose (3 wt%), respectively. With a 6 wt% D-xylose solution, 73% yield was observed. An activity-property correlation of BAIL is established.

Rhodium complex with unsymmetrical vicinal diamine ligand: excellent catalyst for asymmetric transfer hydrogenation of ketones - Deshpande, Sudhindra H.; Shende, Vaishali S.; Shingote, Savita K.; Chakravarty, Debamitra K.; Puranik, Vedavati G.; Chaudhari, Raghunath V.; Kelkar, Ashutosh A. (RSC Advances, 2015)
New unsymmetrical vicinal diamine ligands with systematic variation in the regio and stereo positions in the amine and sulphonamide groups were synthesized from cheap starting material such as norephedrine. Catalytic Asymmetric Transfer Hydrogenation (ATH) of aromatic alkyl ketones has been investigated using transition metal complexes and new derivatives of monotosylated unsymmetrical vicinal diamine ligands using sodium formate as the hydrogen source, in water and methanol. Chiral secondary alcohols were obtained with excellent enantioselectivity (>95% ee) and conversion of ketones (>95%) with [Rh(Cp*)Cl-2](2) and ligand 4 as a catalyst. Enantioselectivity was found to be slightly higher with the use of methanol as a solvent for ATH of ketones with sodium formate as the hydrogen source compared to water as a solvent and was found to be consistent with all the ketones investigated. The reaction mixture is homogeneous in methanol unlike in water, where substrate and product are insoluble in water and form separate phase, sodium formate being soluble in water. The activity and enantioselectivity obtained for ATH of ketones using [Rh(Cp*)Cl-2](2) and unsymmetrical vicinal diamine ligand as catalyst was comparable with the C2 symmetric benchmark ligands like TsDPEN ((1R, 2R)-N-(p-tolylsulfonyl)-1,2-diphenylethylene- diamine), and TsCYDN ((1R, 2R)-N-(p-tolylsulfonyl)-1,2-cyclohexyl, diamine) under similar reaction conditions. To the best of our knowledge, this is first example of the ATH of ketones with good activity and high enantioselectivity with [Rh(Cp*)Cl-2](2) and unsymmetrical vicinal diamine ligands as catalyst systems.

Room-temperature asymmetric transfer hydrogenation of biomass-derived levulinic acid to optically pure gamma-valerolactone using a ruthenium catalyst - Shende, Vaishali S.; Raut, Amol B.; Raghav, Prathamesh; Kelkar, Ashutosh A.; Bhanage, Bhalchandra M. (ACS Omega, 2019)
This study presents a first report on ruthenium-catalyzed asymmetric transfer hydrogenation (ATH) of levulinic acid (LA) to chiral gamma-valerolactone (GVL). ATH of LA has been explored with Noyori's chiral catalyst (Ru-TsDPEN) in methanol solvent. Efficacy of ATH reaction of LA was investigated under different reactions conditions such as temperature, catalyst, and hydrogen donor concentration. The effect of various organic tertiary bases along with formic acid (FA) as a hydrogen donor was studied, and N-methylpiperidine with FA (1:1 molar ratio) was revealed as an efficient hydrogen donor for ATH of LA to GVL furnishing chiral GVL with complete conversion and 93% enantiomeric excess (ee). This operationally simple and mild ATH protocol was tested for practical applicability of ATH of LA obtained from biomass waste (rice husk and wheat straw) and furnished chiral GVL with 82% ee.